A survey study on the contamination of broiler feed with Ochratoxin A in Duhok Governorate, Iraq - Niwar Bari (Basrah Journal of Veterinary Research)
Ochratoxin A (OTA) contamination in broiler chicken feed poses significant risks to animal health and food safety. This study aimed to assess OTA contamination levels in broiler feed samples collected from broiler farms in Duhok Governorate, Kurdistan Region, Iraq, over four years (2020–2023). A total of 292 feed samples were analyzed using an enzyme-linked immunosorbent assay (ELISA) to quantify OTA concentrations. The results revealed a high prevalence of OTA contamination across all years, with 86.8%, 93.8%, 100%, and 96.9% of samples testing positive in 2020, 2021, 2022, and 2023, respectively. The mean OTA concentration showed a declining trend, from 2.615 µg/kg in 2020 to 0.8396 µg/kg in 2023. Statistical analysis using one-way ANOVA confirmed a significant reduction in OTA levels over the years (p < 0.05), indicating improvements in feed safety management. However, variability in OTA concentrations remained high, emphasizing the need for stringent monitoring and preventive measures. The persistence of OTA in poultry feed highlights potential risks for animal health and its possible transfer to poultry products, raising public health concerns. These findings highlight the necessity of continuous surveillance, improved storage practices, and effective detoxification strategies to mitigate OTA contamination in broiler feed. Future studies should employ HPLC for more accurate OTA quantification, as ELISA, while efficient, may cross-react with other metabolites.